Vagus Nerve Stimulation in the treatment of Epilepsy: Our initial experience - Jha, Rajiv; Shrestha, Rajendra; Rajbhandari, Binod; Bhattarai, Sushil Mohan; Aryal, Sameer; Jha, Binit; Karki, Anuj Jung; Gautam, Sindhu (Nepal Journal of Neuroscience, 2024)
Vagus nerve stimulation (VNS) is a neuromodulation therapy which is used to treat intractable seizures not responding well with antiepileptic drugs.This procedure involves the implantation of a device that delivers electrical impulses to the vagus nerve, which in turn modulates neural activity in the brain, potentially reducing the frequency and severity of seizures. Vagal nerve stimulation (VNS) was first approved for treating partial epilepsy but is now showing promise for various seizure disorders, including generalized epilepsy and Lennox-Gastaut syndrome. The exact mechanism of this device is unclear, but it is believed to work at multiple levels, initially by desynchronizing brain activity. Implanting the VNS device is generally safe, with infection being the most common complication. Vocal cord paralysis is the primary neurological issue post-implantation,alongside transient effects like hoarseness, cough, and nausea, which typically don't require stopping treatment.